Comparison of AGNES (absence of gradients and Nernstian equilibrium stripping) and SSCP (scanned stripping chronopotentiometry) for trace metal speciation analysis - Domingos, R. F. (2013)
The free metal ion concentrations obtained by SSCP (stripping chronopotentiometry at scanned deposition potential) and by AGNES (absence of gradients and Nernstian equilibrium stripping) techniques have been compared and the usefulness of the combination of both techniques in the same electrochemical cell for trace metal speciation analysis is assessed. The free metal ion concentrations and the stability constants obtained for lead(II) and cadmium(II) complexation by pyridinedicarboxylic acid, by 40 nm radius carboxylated latex nanospheres and by a humic acid extracted from an ombrotrophic peat bog were determined. Whenever possible, the free metal ion concentrations were compared with the theoretical predictions of the code MEDUSA and with the free metal ion concentrations estimated from ion selective electrodes (ISE). SSCP values were in agreement with the ones obtained by AGNES, and both of them agreed reasonably with the ISE values and the theoretical predictions. For the lead(II)-humic acid, it was not possible to obtain the stability constants by SSCP due to the heterogeneity effect. However, using AGNES it is possible to obtain, for these heterogeneous systems, the free bulk metal concentration, which allows us to retrieve the stability constant at bulk conditions.